INTEGRASI-INTERKONEKSI PERAN PERGURUAN TINGGI DALAM MENINGKATKAN KEMAMPUAN ENTREPRENEUR SKILL DAN MEMPERSIAPKAN COMPETITIVE ADVANTAGE DUNIA KERJA ERA DIGITAL SOCIETY 5.0 - Zathu Restie Utamie; Muhammad Iqbal Fasa (LPPM Universitas Multi Data Palembang, 2023)
Entrepreneurship education plays an important role in the development of entrepreneurial skills in individuals. It is time for universities based on teaching methods to switch to practicing methods, whose main focus is practical experience (practical work experience). This study used qualitative research methods. The results of this study found that UIN Raden Intan Lampung carried out various programs including: (1) Job Seeking Activities; (2) Entrepreneurship Training Activities; (3) Population Education Implementation Activities Through Compulsory General Lecture Materials (MKWU); (4) JOB FAIR activities; (5) Activities to prepare career center manuals; (6) OJK Teaching Activities to 1,000 students throughout Lampung Province; (7) Tracer Study Activities; (8) Pre-Employment Card Dissemination Assistance Activities; (9) Business Plan competition activities; (10) Webinar Activities